Where is the True Home of Sport? An Analysis of the Locations Chosen by International Sports Governing Bodies (IGBs) To Host Their Headquarters - Creed, A.J (2009)
This dissertation examines why different International Governing Bodies (IGBs) have chosen certain cities around the world in which to locate their headquarters and what resources these particular cities possess that makes them attractive locations.